Analisis Forensik Digital Serangan DoS pada Web Server Menggunakan Metode NIST SP 800-86 dan Suricata IDS - Lilo Wedhar Widyastuti; Aqilah Aulya Maulidah; Yustian Servanda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Dental caries remains a major global oral health challenge, emphasizing the need for effective, biocompatible, and sustainable remineralization agents. This study aimed to synthesize biogenic nanohydroxyapatite (nHAp) from green mussel shell (Perna viridis) waste through a green synthesis approach and evaluate its physicochemical properties for potential dental remineralization applications. Green mussel shells containing 57.23% calcium were utilized as a natural precursor. The shells were calcined at 900°C to convert calcium carbonate into calcium oxide (CaO), followed by a controlled precipitation process and high-energy ball milling to obtain nanoscale particles. The synthesized material was characterized using Energy Dispersive X-Ray Fluorescence (EDXRF), Fourier Transform Infrared Spectroscopy (FTIR), Particle Size Analysis (PSA), X-Ray Diffraction (XRD), and Scanning Electron Microscopy coupled with Energy Dispersive X-Ray Analysis (SEM-EDX). FTIR results confirmed the formation of hydroxyapatite through the presence of phosphate (PO₄³⁻), hydroxyl (OH⁻), and carbonate (CO₃²⁻) functional groups. PSA analysis revealed particle sizes ranging from 40 to 60 nm, with the smallest average size of 40 nm obtained using 12 g CaO. XRD patterns exhibited characteristic hydroxyapatite diffraction peaks at approximately 25.9°, 31.8°, 32.9°, and 34.1° (2θ), indicating high crystallinity and phase purity. SEM observations showed predominantly spherical particle morphology, while EDX analysis produced a Ca/P ratio of 1.80. These findings demonstrate that Perna viridis shell waste is a promising and sustainable source for producing nanohydroxyapatite with favorable physicochemical properties for future dental remineralization applications.